Hidrogéis condutivos nanoestruturados para a liberação tunável de fármacos - Lopes, Rayssa de Souza (Universidade Federal de São Carlos, 2026)
Poly(vinyl alcohol) (PVA)-based hydrogels have been widely investigated for biomedical applications, particularly in controlled drug delivery systems, due to their high swelling capacity, biocompatibility, and ease of structural modification. In this context, the incorporation of conducting polymers and dopant agents emerges as a promising strategy for the development of multifunctional materials with tunable properties, capable of integrating mass transport and electrical response. The present work aimed to develop and characterize conductive hydrogels based on PVA incorporated with polypyrrole (PPy) and poly(o-ethoxyaniline) (POEA), in the presence of the dopant dodecylbenzenesulfonic acid (DBSA), evaluating the effect of ibuprofen and diclofenac sodium incorporation on the structural, thermal, morphological, and electrical properties of the systems. The hydrogels were prepared by physical crosslinking and characterized by differential scanning calorimetry (DSC), swelling tests in distilled water, scanning electron microscopy (SEM), density determination by flotation with subsequent calculation of network parameters using the Flory–Rehner model, and electrochemical impedance spectroscopy. The morphology of the materials was analyzed both qualitatively and quantitatively through pore size distribution, fitted using a log-normal function when applicable. The DSC results indicated that the incorporation of conducting polymers, dopant, and drugs promotes changes in the thermal transitions of PVA, reflecting modifications in structural organization and chain mobility. Swelling tests showed high water absorption capacity for all systems (≈135–180%), modulated by composition, with increased swelling in doped systems and variations associated with drug incorporation. SEM analysis revealed an interconnected porous structure for pure PVA and significant morphological changes in the presence of PPy, POEA, and DBSA, including a reduction in average pore size in drug-loaded systems. In ibuprofen-containing samples, loss of surface definition was observed, attributed to possible drug precipitation, surface coating, or interaction with the polymer matrix, which hindered pore quantification. Network parameters indicated variations in crosslink density and mesh size, corroborating swelling and morphological results. Impedance analysis demonstrated semiconducting behavior and confirmed the formation of conductive pathways within the polymer matrix, especially in doped systems. Overall, the results demonstrate that the combination of PVA with conducting polymers, dopant, and drugs enables modulation of structural, morphological, and electrical properties, resulting in multifunctional hydrogels with potential applications in controlled drug delivery systems and biomedical devices.
Nanostructured conductive hydrogels for tunable drug release
Keywords: Hidrogéis; Polímeros condutores; Liberação controlada; CIENCIAS EXATAS E DA TERRA::QUIMICA; 3. Saúde e Bem-Estar